Latent change variable models in studying intra-individual variability in coping measures - Buško, Vesna (Array, 2004)
The study demonstrates the applicability of a particular class of structural equation models to the study of intraindividual variations in coping with low-control stress. These structural equation models, as put forward by Steyer, Eid, and Schwenkmezer (1997 ; Steyer, Partchev, & Shannahan, 2000) are specified so that the true intraindividual change scores between two occasions of measurement correspond to the values of endogenous latent variables. Such a specification further enables examining correlates and predictors of true intraindividual change between the measurements. According to the transactional stress and coping theory, the processes of coping are context-specific and varying across time and the attributes of concrete stressful situations. Nevertheless, substantial interindividual differences in the intraindividual change scores can still be found in the measures of coping with any kind of situational demands. The true change modeling procedures were hence employed to test the hypotheses on the antecedents and sources of interindividual differences in changes in the use of specific coping strategies. The data analyzed here were collected within follow-up study on the processes of coping and adjustment of recruits during military service (Buško, & Kulenović, 2003). Along with three broad situation-specific coping measures, personality data derived from NEOFFI questionnaire and the cognitive appraisals data, gathered on two occasions on the sample of 421 military basic trainees, were also used in this study. The tested structural equation models and the parameters obtained point to different patterns of relationships of latent state and latent change coping measures with particular personality and appraisals variables. The findings are discussed within the framework of transactional stress and coping theory and the context of low-control stressful situations.